INFORMATION SUPPORT OF THE MARKETING RESEARCH SYSTEM OF THE MINERAL WATER MARKET - TANASIICHUK, ALONA; SEREDNYTSKA, LIUDMILA; DOBROVOLSKA, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
It has been demonstrated that in the conditions of overcoming the consequences of corona crisis an important issue is the organization of business processes, which, as of the time of the study, is carried out on a mixed form. It is substantiated that enterprises should assess their capabilities and be ready to make quick business decisions in the case of reintroduction of quarantine for enterprises. It is substantiated that the organization of marketing research of commodity markets and timely provision of managers of structural units with reliable information is important for the effective conduct of business by domestic enterprises on a mixed form. In the study the sequence of information support for marketing research of the mineral water market has been developed. The dynamics of incomes and the level of demand of mineral water consumers during the period of corona crisis has been determined. As a result of the research it was concluded that the mineral water market, unlike other sectors of the economy, has favorable prospects for further development. A portrait of a mineral water consumer and his level of satisfaction with the quality of mineral water, pricing and assortment policy on the domestic market have been determined. This study will determine consumer preferences for the choice of mineral water and take into account its results by domestic production and trade enterprises. Other enterprises will be able to develop a similar sequence of information support for marketing research of the commodity market in which they carry out their business activities.